VD_FINDINFO HC / 2012 / 696 vom 2. Oktober 2012 - VD Tribunal cantonal (2012)
PRÊT DE CONSOMMATION, APPRÉCIATION DES PREUVES, NATURE JURIDIQUE | 312 CO, 157 CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)